ANALISIS KEMAMPUAN METAKOGNISI SISWA DALAM MEMECAHKAN MASALAH MATEMATIS DI SMPN 3 X KOTO SINGGALANG KABUPATEN TANAH DATAR DITINJAU DARI GENDER - Risda Weni; Elda Herlina; Nola Nari (AGENDA: Jurnal Analisis Gender dan Agama, 2019)
The lack of students’ awareness and comprehension in solving math problems was the research background. The teacher only emphasizes the results and does not evaluate the process of students’ cognitive aspects and their awareness in answering the questions. The purpose of this research is to figure out how the metacognition abilities of male and female students solve math problems. The research design was descriptive research. The techniques of data collection were a test for measuring students’ metacognition ability in solving math problems, students’ worksheet, and interview. Then, it was analyzed through scoring procedures, tabulating data and determining the category of metacognition abilities. Meanwhile, the data from interview were analyzed by conducting several procedures such as reducing data, providing data, and drawing conclusions. The research results showed there were no differences in the metacognition abilities between male and female students.